The Effect of Transformational Leadership and Servant Leadership on Employee Performance Through Organizational Commitment as an Intervening Variable in The Government of The Riau Islands Province - Antony Sentoso; Taqiyuddin Taqiyuddin; Yulfiswandi Yulfiswandi (Dinasti International Journal of Education Management And Social Science, 2025)
Employee performance is an important element that affects how effective and successful an organization is, especially in the government sector. This study emphasizes the significance of leadership in enhancing employee performance with organizational commitment as a factor influencing this relationship. Effective leadership may establish a clear goal, foster trust, and enhance staff morale. Respondents in this quantitative study were ASN in the Riau Islands Provincial Government, with data processing using Smart PLS. Filling out questionnaires sent via Google Form is the main method of primary data collection in this study. The results of the study indicate that Transformational Leadership and Servant Leadership have a positive and significant effect on Organizational Commitment, Organizational Commitment and Transformational Leadership have a positive and significant effect on employee performance, while Servant Leadership does not affect Employee Performance. The relationship between transformational leadership and employee performance, as well as between servant leadership and employee performance, is significantly mediated by organizational commitment.